2018
DOI: 10.3389/fpls.2018.01341
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Rice Tolerance Mechanisms Against Schizotetranychus oryzae Mite Infestation

Abstract: Rice is the staple food for over half of the world’s population. Infestation of Schizotetranychus oryzae (Acari: Tetranychidae) causes great losses in rice productivity. To search for rice genotypes that could better tolerate S. oryzae infestation, we evaluated morphological and production parameters in Brazilian cultivars, and identified two cultivars with contrasting responses. Leaf damage during infestation was similar for all cultivars. However, infestation in Puitá INTA-CL resulted in reduction in the num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…The reduction of photosynthesis may be induced by either direct mesophyll damage and a significant reduction in stomatal conductance (Fadini et al 2004) or disorders in the transcription and translation of proteins associated with the photosynthetic apparatus (Schmitt et al 2014) or disruptions in the synthesis pathway of chlorophylls and carotenoids (Bronner et al 1991). It was shown that reduced photosynthesis efficiency in rice plants can be caused not only by a decrease in chlorophyll content (Buffon et al 2016(Buffon et al , 2018 but also by down-regulation of seven proteins synthesis related to NADPH production and thus to adenosine triphosphate and glucose synthesis (Blasi et al 2017). In the presented experiment, however, no significant differences were observed in the efficiency of photosynthesis (PN), transpiration (E), as well as in stomatal conductance (Gs) between barley plants inoculated and uninoculated with CCN and WCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of photosynthesis may be induced by either direct mesophyll damage and a significant reduction in stomatal conductance (Fadini et al 2004) or disorders in the transcription and translation of proteins associated with the photosynthetic apparatus (Schmitt et al 2014) or disruptions in the synthesis pathway of chlorophylls and carotenoids (Bronner et al 1991). It was shown that reduced photosynthesis efficiency in rice plants can be caused not only by a decrease in chlorophyll content (Buffon et al 2016(Buffon et al , 2018 but also by down-regulation of seven proteins synthesis related to NADPH production and thus to adenosine triphosphate and glucose synthesis (Blasi et al 2017). In the presented experiment, however, no significant differences were observed in the efficiency of photosynthesis (PN), transpiration (E), as well as in stomatal conductance (Gs) between barley plants inoculated and uninoculated with CCN and WCM.…”
Section: Discussionmentioning
confidence: 99%
“…All these limitations lead to generation of ROS, RNS and organic radicals causing irreversible destruction of the photosynthetic apparatus (Kalaji et al 2016;Tokarz et al 2020a). Kinetic of chl a fluorescence revealed that rice plants sensitive to mite feeding had a significantly lower number of open PSII RC (F 0 ) among all PSII RC (Vj) as well as significantly lower efficiency of trapped energy flux (TRo/ CSo) compared to resistant plants (Buffon et al 2018). At the same time, sensitive cultivars dissipated more intensely part of the trapped energy (Dio/RC) (Buffon et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of damage caused by S. oryzae was analyzed from V10-13 stage until the plants reached the final stage of reproductive development (panicle maturity, R9 stage; Counce et al, 2000 ). Evaluation of damage in the abaxial and adaxial faces of leaves was based on a classification of four infestation levels: Level 1: control condition, without any sign of infestation; Level 2: early infested (EI) leaves, 10–20% of damaged leaf area, average of 168 h of exposure to the mite; Level 3: intermediate infested (II) leaves, 40–50% of damaged leaf area, average of 360 h; and Level 4: late infested (LI) leaves, more than 80% of damaged leaf area, average of 720 h, according to Buffon et al (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Most of these losses (13–16%) occur in the field before harvesting, and losses are most often described in developing countries ( Culliney, 2014 ). One of the arthropods that attack rice crops in Brazil, and has been reported in other South American countries, is Schizotetranychus oryzae Rossi de Simons mite species, which can cause more than 60% loss in rice grain yield ( Buffon et al, 2018 ). An interesting strategy for reducing these losses is the search for mite-tolerant cultivars, as these plants tolerate mite infestation and maintain grain yield without the need to apply acaricides ( Sperotto et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%